165k views
2 votes
PLEASE SOLVE
1/3 (12f-3)=4f-1

User Yash Mochi
by
5.3k points

2 Answers

5 votes

Answer:

f = 0

No solution

Explanation:


(1)/(3) (12f - 3) = 4f - 1

Use to open the bracket


(1)/(3) * \: 12f = 4f \\ (1)/(3) * 3= </strong><strong>1</strong><strong>


4f - </strong><strong>1</strong><strong>= 4f - 1

Collect like terms


4f - 4f = - 1</strong><strong>+</strong><strong>1</strong><strong> \\ - 1f = </strong><strong>0</strong><strong> \\ \\ f = </strong><strong>0</strong><strong>

User Geoffrey Fook
by
5.4k points
0 votes

Answer:

4F-1

Theres infinite amount of solutions

Explanation:

12f/3=4f

-3/3=-1

4f-1=4f-1

User Ralfs
by
5.4k points